Desiccation as a mitigation tool to manage biofouling risks: trials on temperate taxa to elucidate factors influencing mortality rates. Issue 1 (2nd January 2016) - Hopkins, Grant A.; Prince, Madeleine; Cahill, Patrick L.; Fletcher, Lauren M.; Atalah, Javier
Abstract: The desiccation tolerance of biofouling taxa (adults and early life-stages) was determined under both controlled and 'realistic' field conditions. Adults of the ascidian Ciona  spp. died within 24 h. Mortality in the adult blue mussel Mytilus galloprovincialis occurred within 11 d under controlled conditions, compared with 7 d when held outside. The Pacific oyster Crassostrea gigas was the most desiccation-tolerant taxon tested (up to 34 d under controlled conditions). Biofouling orientated to direct sunlight showed faster mortality rates for all the taxa tested. Mortality in Mytilus juveniles took up to 24 h, compared with 8 h for Ciona, with greater survival at the higher temperature (18.5°C) and humidity (~95% RH) treatment combination. This study demonstrated that desiccation can be an effective mitigation method for a broad range of fouling taxa, especially their early life-stages. Further work is necessary to assess risks from other high-risk species such as algae and cyst forming species.